Hutchinson-Gilford progeria syndrome alters nuclear shape and reduces cell motility in three dimensional model substrates - Booth-Gauthier, Elizabeth A.; Du, Vicard; Ghibaudo, Marion; Rape, Andrew D.; Dahl, Kris Noel; Ladoux, Benoit (Integrative Biology, 2013)
Cell migration through tight interstitial spaces in three dimensional (3D) environments impacts development, wound healing and cancer metastasis and is altered by the aging process. The stiffness of the extracellular matrix (ECM) increases with aging and affects the cells and cytoskeletal processes involved in cell migration. However, the nucleus, which is the largest and densest organelle, has not been widely studied during cell migration through the ECM. Additionally, the nucleus is stiffened during the aging process through the accumulation of a mutant nucleoskeleton protein lamin A, progerin. By using microfabricated substrates to mimic the confined environment of surrounding tissues, we characterized nuclear movements and deformation during cell migration into micropillars where interspacing can be tuned to vary nuclear confinement. Cell motility decreased with decreased micropillar (μP) spacing and correlated with increased dysmorphic shapes of nuclei. We examined the effects of increased nuclear stiffness which correlates with cellular aging by studying Hutchinson-Gilford progeria syndrome cells which are known to accumulate progerin. With the expression of progerin, cells showed a threshold response to decreased μP spacing. Cells became trapped in the close spacing, possibly from visible micro-defects in the nucleoskeleton induced by cell crawling through the μP and from reduced force generation, measured independently. We suggest that ECM changes during aging could be compounded by the increasing stiffness of the nucleus and thus changes in cell migration through 3D tissues. © 2013 The Royal Society of Chemistry.
CRIS-Team Scopus Importer:2024-02-19